Improvement of Lipoprotein Profile and Metabolic Endotoxemia by a Lifestyle Intervention That Modifies the Gut Microbiota in Subjects With Metabolic Syndrome - Guevara‐Cruz, Martha; Flores‐López, Adriana G.; Aguilar‐López, Miriam; Sánchez‐Tapia, Mónica; Medina‐Vera, Isabel; Díaz, Daniel; Tovar, Armando R.; Torres, Nimbe (Journal of the American Heart Association, 2019)
Background Metabolic syndrome (MetS) is a serious health problem over the world; thus, the aim of the present work was to develop a lifestyle intervention to decrease the dysbiosis of gut microbiota and reduce the biochemical abnormalities of MetS. Methods and Results The prevalence of MetS was evaluated in 1065 subjects of Mexico City, Mexico, and the gut microbiota in a subsample. Subjects with MetS were selected for a pragmatic study based on a lifestyle intervention with a low-saturated-fat diet, reduced-energy intake, with functional foods and physical activity, and a second group was selected for a randomized control-placebo study to assess the gut microbiota after the dietary intervention. Prevalence of MetS was 53%, and the higher the body mass index, the higher the gut microbiota dysbiosis. The higher the Homeostatic Model Assessment for Insulin Resistance, the lower the high-density lipoprotein cholesterol concentration. The pragmatic study revealed that after 15 days on a low-saturated-fat diet, there was a 24% reduction in serum triglycerides; and after a 75-day lifestyle intervention, MetS was reduced by 44.8%, with a reduction in low-density lipoprotein cholesterol, small low-density lipoprotein particles, glucose intolerance, lipopolysaccharide, and branched-chain amino acid. The randomized control-placebo study showed that after the lifestyle intervention, there was a decrease in the dysbiosis of the gut microbiota associated with a reduction in the Prevotella/ Bacteroides ratio and an increase in the abundance of Akkermansia muciniphila and Faecalibacterium prausnitzii. Conclusions A lifestyle intervention significantly decreased MetS components, small low-density lipoprotein particle concentration, gut microbiota dysbiosis, and metabolic endotoxemia, reducing the risk of atherosclerosis. Clinical Trial Registration URL: https://www.clinicaltrials.gov. Unique identifier: NCT03611140.